2006
DOI: 10.1074/jbc.m506164200
|View full text |Cite
|
Sign up to set email alerts
|

Gerstmann-Sträussler-Scheinker Disease Amyloid Protein Polymerizes According to the “Dock-and-Lock” Model

Abstract: Prion protein (PrP) amyloid formation is a central feature of genetic and acquired prion diseases such as Gerstmann-Sträussler-Scheinker disease (GSS) and variant Creutzfeldt-Jakob disease. The major component of GSS amyloid is a PrP fragment spanning residues ϳ82-146, which when synthesized as a peptide, readily forms fibrils featuring GSS amyloid. The present study employed surface plasmon resonance (SPR) to characterize the binding events underlying PrP82-146 oligomerization at the first stages of fibrilliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
(44 reference statements)
4
24
0
Order By: Relevance
“…These results can be interpreted by assuming that before pressure treatment two populations of PrP fibrils coexist in the sample; that is, a "partially locked" (reversibly bound monomers) form that can be dissociated and a "totally locked" form (irreversibly bound monomers) that cannot be dissociated. These two conformers are currently thought to be different states occurring during amyloidogenesis (73)(74)(75)(76). Yet the structural differences between these two initial and co-existing populations of fibrils appear to be subtle.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be interpreted by assuming that before pressure treatment two populations of PrP fibrils coexist in the sample; that is, a "partially locked" (reversibly bound monomers) form that can be dissociated and a "totally locked" form (irreversibly bound monomers) that cannot be dissociated. These two conformers are currently thought to be different states occurring during amyloidogenesis (73)(74)(75)(76). Yet the structural differences between these two initial and co-existing populations of fibrils appear to be subtle.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of aggregation of PrP 82-146 was investigated by Gobbi et al (2006), who proposed a "dock-and-lock" model to explain the mechanism of polymerization. Structural analysis found profound differences between the wild-type and partially scrambled PrP 82-146 peptides in their propensity to aggregate , amyloid formation being significantly reduced or prevented when either region 106 -126 or 127-146 was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of these advances, we have performed all-atom MD simulations to describe the molecular events in the growth process of amyloid fibrils. Several experiments have suggested that the kinetics of monomer incorporation is complex but can be described by a dock-lock mechanism (19,(33)(34)(35). In this scenario, which can be rationalized by using an energy landscape perspective (36, 37), the addition of the monomer is envisioned to occur in 2 distinct global stages.…”
mentioning
confidence: 99%